TINJAUAN ATAS PROSEDUR PEMBAYARAN UTANG USAHA TERHADAP SUPPLIER PADA CV. PUTRA SAMA - Nadila Wahyu Saputri (2022)
The purpose of writing this Final Project is to determine the procedure for paying accounts payable on a CV. Putra Sama is engaged in trading. The method for the payment of invoices payable is a crucial stage required by the company to support the smooth running of the business. Accounts payable occur after the company makes a purchase transaction and is then paid on credit. To minimize errors in the payment of accounts payable, several supporting documents are needed to facilitate the payment process for accounts payable, including purchase notes, invoices, proof of deposit, and receipts. Then the parties related to the payment of trade payables are also needed, such as the warehouse, administration, and finance divisions-completion of trade payables made by CV. Putra Sama has two methods: direct deposit to the bank and billet giro. On CV. Putra Sama, payment of trade payables follows the procedures applied so that the company is exceptionally good at paying trade debts because, in its implementation, it already has the correct procedures following the rules